Altruism and beyond : an economic analysis of transfers and exchanges within families and groups - Stark, Oded (Oscar Morgenstern memorial lectures., 1995)
This book employs economic methodology to study the motives for and the repercussions of transfers and exchanges within families, between generations, and within groups. The book shows how the allocative behavior and wellbeing of one family member depend on his altruistic link with another family member, how the timing of the intergenerational transfer of the family productive asset affects the recipient's incentive to engage in human capital formation, and how transfers from an adult to his parents impinge on future transfers to him from his own children. In addition, the book shows that under asymmetric information high-skill migrant workers make transfers to low-skill would-be migrants in order to lure them to stay put, and that under incomplete information a group-specific informational edge - lower recognition costs - results in a superior exchange outcome.